The Effect of Cultural Differences in Translating Stylistic Features between Arabic and English - Hannawi, Amira Rifae (جامعة تكريت - كلية الآداب, 2023)
The main problem that the translators face is the cultural difference between the two languages. This study is clarified the significance of stylistics, as a well-known literary phenomenon, and its effect of the cultural differences. The study aims to investigate translation difficulties that encounter literary translators due to cultural and stylistic features when translating literary texts. The findings of the study revealed that literary translators encounter serious problems when translating literary texts because of differences between cultures and beliefs. In the light of the findings of the study, the researcher recommends that literary translators should have a good grasp of literary genres in both languages and they should consider both cultural and linguistic elements.
Keywords: الاختلافات الثقافية -- الترجمة الأدبية -- المترجمون الأدبيون